Hubungan Kesehatan Mental dan Prestasi Belajar Remaja Stunting - Lutiyah, Lutiyah; Martini, Eva; Fauziyah, Sifa; Nurhilmiah, Tia (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Adolescence is a time of searching for character. There are many factors that influence its growth and development. One of them is nutritional intake, insufficient nutritional intake can result in stunting which then affects children's motoric, psychological and cognitive development. One of the psychological problems that arises is mental health problems and cognitive problems, namely learning achievement. This research is to determine the relationship between mental health and the learning achievement of stunted adolescents. The research used a quantitative approach with Spearman Rank correlation analysis, a sample of 73, total sampling method. Measuring tools use the Strength and Difficulties Questionnaire (SDQ), anthropometry and documentation of report cards. This research has a Spearman correlation coefficient value of 0.669, indicating a strong positive relationship between mental health and the learning achievement of stunted adolescents. Good mental health will support good learning achievement.  Keywords: Mental Health, Learning Achievement, Teenagers, Stunting  ABSTRAK Masa remaja adalah masa mencari karakter. Ada banyak faktor yang mempengaruhi pertumbuhan dan perkembangannya. Salah satunya adalah asupan gizi, asupan gizi yang kurang bisa mengakibatkan stunting yang kemudian berpengaruh terhadap penkembangan motorik, psikologis dan kognitif anak. Salah satu masalah psikologis yang muncul yaitu masalah kesehatan mental dan untuk kognitif yaitu prestasi belajar. Penelitian ini adalah untuk mengetahui hubungan antara kesehatan mental dengan prestasi belajar remaja stunting. Penelitian menggunakan pendekatan kuantitatif dengan analisa korelasi Spearman Rank, sampel sebanyak 73, metode pengambilan sampel total sampling. Alat ukur menggunakan Strenght and difficulties Questionnare (SDQ), antropometri dan dokumentasi nilai rapot.  Penelitian ini memiliki nilai koefisien korelasi Spearman 0,669, menunjukkan hubungan positif yang kuat antara kesehatan mental dan prestasi belajar remaja stunting. Kesehatan mental yang baik akan mendukung prestasi belajar yang baik. Kata Kunci: Kesehatan Mental, Prestasi Belajar, Remaja, Stunting